(untitled) (Biological Sciences - PJSIR, 2009)
The oils extracted from raw seeds of Cicer arietinum and Vigna mungo of different areas of Punjab province of Pakistan were found to possess, more or less, the same physicochemical properties and fatty acid composition. The oils of both the grains showed an increase in the peroxide and free fatty acids values after both, sand and microwave roasting. Other physicochemical values did not show any significant change in the roasted seed oils. The oils of Vigna mungo showed a higher concentration of unsaturated fatty acids. The oils of both the species had a significant amount of linoleic acid in raw, microwave and sand roasted seeds.